181 SAFETY AND EFFICACY OF SUBCUTANEOUS IMPLANTABLE CARDIOVERTER-DEFIBRILLATORS LEAD REMOVAL: A SINGLE CENTER EXPERIENCE. (15th December 2022) - Pittorru, Raimondo; Bernardo Dall´aglio, Pietro; Valerio Falzone, Pasquale; Giacomin Lazzari, Enrico; De, Manuel; Iliceto, Sabino; Migliore, Federico
Abstract: The aim of this monocentric experience was to evaluate the efficacy and safety of subcutaneous implantable cardioverter-defibrillators (S-ICDs) lead removal procedures. Background: S-ICD represents a therapeutic option for patients at high-risk of sudden cardiac death, in whom pacing or cardiac resynchronization therapy is not required. Furthermore, S-ICD is a suitable alternative in patients who had underwent to transvenous lead extraction, expecially to limit lead-related complications of transvenous ICD. However, data are lacking about the safety and feasibility of S-ICD lead removal procedures. Methods: We enrolled a population consisted of 11 consecutive patients requiring S-ICD lead removal between May 25, 2014, and June 26, 2022. The primary endpoint of the study was procedural success, defined as the removal of all the lead and lead material from the subcutaneous space. Secondary endpoints included procedural complications and the need for specific removal tools. Results: S-ICD lead removal procedures were performed in 11 patients (mean age 47 ± 14, 82% men, 64% in primary prevention). Indications for S-ICD removal procedures were replace with inappropriate sensing (n=2), generator and lead infection (n= 3), pocket erosion (n=1), system malfunction (n=2), ineffective therapy (n=1) and, finally, heart transplantation (n=2). The median time from S-ICD lead implantation to S-ICD removal was 16 (6-38) months. The primary endpoint was achieved in 100% of the patients, without procedural failure. Simple traction of the S-ICD lead was successful in 8 patients (73%), whereas 3 patients (27%) required non-powered mechanical sheath to remove lead adhesions around the coil. No addictional incision were needed in order to lead removal. No procedure-related complications occurred. Patients with device infection underwent to S-ICD removal earlier than patients without (11 months [6.5 to 15.2 months ] vs 31 months [16.5 to 45.5 months]). Conclusions: Although simple manual traction is effective in most patients, additional tools are required in few cases, raising the question, if also the S-ICD lead removal should performed in centers with lead extraction experience with available advanced tools.